2010
DOI: 10.1007/s00198-010-1386-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for peripheral fractures vary by age in older men—the prospective MINOS study

Abstract: Men aged ≤ 65 with multiple prevalent fractures and frequent fallers aged >65 are at particularly high risk of peripheral fracture regardless of BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Blaizot et al . reported that although previous osteoporotic fracture was the most important predictor of future fractures in those aged ≤65 years, it was falls in those aged >65 years . However, that study included only males, and the outcome measure was not specific for hip fracture.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Blaizot et al . reported that although previous osteoporotic fracture was the most important predictor of future fractures in those aged ≤65 years, it was falls in those aged >65 years . However, that study included only males, and the outcome measure was not specific for hip fracture.…”
Section: Introductionmentioning
confidence: 97%
“…Blaizot et al reported that although previous osteoporotic fracture was the most important predictor of future fractures in those aged Յ65 years, it was falls in those aged >65 years. 10 However, that study included only males, and the outcome measure was not specific for hip fracture. Taylor et al found no differences in hip fracture risk factors between women aged <75 years and Ն75 years, but the study did not report relevant descriptive details, such as the number of participants in the Ն75 age group.…”
Section: Introductionmentioning
confidence: 99%
“…Low bone mineral density (BMD) measured by dual‐energy X‐ray absorptiometry (DXA) identifies fewer men at high risk of fracture compared with women 1–3. History of fracture, history of fall, and severe abdominal aortic calcification (AAC) may improve fracture prediction; however, data are not fully consistent 4–6. Biochemical bone turnover markers (BTM), quantitative computed tomography, and ultrasounds do not improve fracture prediction in men compared with BMD 7–10.…”
Section: Introductionmentioning
confidence: 99%
“…It takes into account history of fractures and that of falls. Falls, especially multiple falls, seem to be associated with a substantial increase in the risk of peripheral fracture in the elderly men [26]. However, both FRAX and the Garvan nomogram have been introduced only recently and few studies assessed their utility in men [27, 28].…”
mentioning
confidence: 99%
“…In men, the parameter that indicates higher risk of fracture most consistently in epidemiological studies is prevalent fragility fracture [26, 57]. A history of osteoporotic fracture is associated with a two- to fourfold higher risk of another osteoporotic fracture.…”
mentioning
confidence: 99%